PERAN KETERAMPILAN KOMUNIKASI VERBAL ANTAR BUDAYA DALAM MENINGKATKAN TOLERANSI BERAGAMA DI SMPN 237 JAKARTA - Fadylah Annisa; Fauzan Fahru Ramadhan; Alivia Salsabila; Arga Sabda Wiguna; Ahmad Ridwan (Jurnal Cakrawala Ilmiah, 2024)
Indonesia is a country rich in cultural, ethnic, and religious diversity. This diversity is both an asset and a challenge in maintaining harmony amidst differences. One important element that creates harmony in a multicultural society is tolerance, which can be enhanced through intercultural verbal communication. This study aims to analyze the role of intercultural verbal communication in improving religious tolerance at SMPN 237 Jakarta, identify barriers and supporting factors in the effectiveness of verbal communication, and explore the perspectives of students from various religions, especially Islam and non-Islam, regarding the importance of communication in building tolerance. The research method used is mixed methods with a sequential exploratory design. This approach begins with collecting qualitative data through in-depth interviews to understand the phenomenon in detail, which is then complemented by quantitative data through distributing questionnaires to obtain more measurable results. Based on data analysis, it was found that barriers to verbal communication include differences in religious beliefs, ethnocentrism, racism, social prejudice, and discrimination. Supporting factors include cultural awareness, empathy, an open attitude, and an inclusive school environment. The results of this study are expected to provide theoretical contributions to the development of intercultural communication studies and practical benefits for educators, students, and educational institutions. The findings can be the basis for creating a tolerant and harmonious school environment, thereby supporting the creation of a young generation who appreciates diversity, can think critically, and has good communication skills to create a peaceful life.